PENGARUH PENGALAMAN KERJA, KETERAMPILAN, DISIPLIN DAN KOMPENSASI TERHADAP PRODUKTIVITAS PEGAWAI PADA SEKRETARIAT KABUPATEN KUTAI TIMUR - Adi Suroso, Ismawati Titin Ruliana (EKONOMIA, 2016)
Measurement of labor productivity is one way to improve productivity, where the measurement results will be used as a reference to see employee productivity in the past by looking at the deficiencies that exist to be improved in the future so that employee productivity in the future can increased. The good productivity is influenced by several things, such as work experience, skills, discipline and compensation.The purpose of this study was to determine whether work experience, skills, discipline and compensation significant effect on the productivity of employees and to determine whether the compensation the most significant effect on the productivity of employees at the East Kutai Regency Secretariat.